Impact of Capital Structure on the Company’s Financial Situation during the Pandemic – Analysis Based on Examples of Listed Companies - Jasiniak, Magdalena; Rudzki, Mateusz (Journal of Finance and Financial Law, 2023)
Under the conditions of increased uncertainty making right financial decisions can determine success or failure of every company. Maintaining financial liquidity is especially important during impactful economic fluctuations when the risk of bankruptcy rises significantly. The purpose of the article is to evaluate the impact of financing strategies on economic situation of companies during the pandemic as well as to verify whether safe strategy can be a reliable measure of protection from the danger of bankruptcy. Methodology. Empirical research has been based on the analysis of 30 commercial sector companies’ financial statements from 2018 to 2020. The research has been completed with discriminant analysis models, and in order to receive clear interpretation of results a new indicator has been created. The indicator shows effectiveness of financing strategies as protection from negative results of the pandemic. Results of the research prove that under the conditions of strong and rapid economic changes a conservative strategy is a relatively safer strategy than moderate and aggressive ones, yet, it does not guarantee full protection from bankruptcy. Additionally, moderately higher risk of financing allows to increase liquidity and profitability even during the pandemic which was also indicated in the research.